Surgical Site Infection after Intra-Abdominal Surgery in Bamrasnaradura Infectious Institute - ว่องธวัชชัย ประสงค์; โชตนะพันธ์ สุทัศน์; จิระมานะพันธ์ ตันภัย (Disease Control Journal, 2007)
Surgical site infection (infection that occurs at surgical wound; SSI) is one of the morbidity and mortality in surgical patients. The incidence of infection varies from surgeon to surgeon, from hospital to hospital, from one surgical procedure to another and from one patient to another. This study reported the incidence of surgical site infection among the patients who had abdominal surgery in Bamrasnaradura Infectious Institute between years 2004 to 2006. The study found that there were 15 cases of SSI. Most of the cases were operated as emergency cases and all had contaminated wounds (wounds were contaminated by bowel contents during surgery). Beside the contaminated wounds, all patients’ wounds were closed as primary closure. We concluded that surgeons should be aware of wounds infection in this group of patients and their wounds should treat as a delay primary suture wound.